Features of Neuroimaging Diagnostics of Transient Ischemic Attacks - Muborak B. Abdullaeva1, Yoqutkhon N Majidova2, Malika M. Raimova3, Nozima R. Babadjanova4, Umida G. (Institute of Medico-legal Publications Pvt Ltd, 2020)
Transient ischemic attacks (TIA), as precursors of cerebral strokes, occupy an important place among allforms of cerebrovascular insufficiency. Regarding epidemiology of transient ischemic attacks (TIA), thereare no accurate data in most countries. In the United States, up to 5 million adult citizens per year suffer fromthese episodes, many TIA remain undiagnosed. These episodes of a sudden and short-term neurological deficithave long been considered as benign and harmless. Most general practitioners and patients misunderstandor insufficiently understand TIA’s nature and significance, perhaps, this is the reason of insufficient medicalinterest, lack of statistical data on this nosological unit. Transient ischemic attacks (TIA) are clinicallydefined as rapidly developing focal and sometimes diffuse (cerebral) dysfunctions of the brain that arecaused by local ischemia and last no longer than a day1. Over the past two decades, many views on TIA havechanged significantly, approaches to the diagnosis and treatment of patients have become much more intenseand aggressive. Modern knowledge about TIA is of paramount importance both for proper organization ofpatient care and educational programs among the population; their importance can hardly be overestimated.